ANALISIS PENERAPAN ENVIROMENTAL MANAGEMENT ACCOUNTING (EMA) PADA RSUD DR.H.SLAMET MARTODJIRJO PAMEKASAN - Halimatus Sakdiyah (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2017)
The negative impacts caused by the hospital require the environmental accounting system as the control of the organization's responsibility because the waste management conducted by the hospital requires measurement, assessment, disclosure and reporting of waste management cost from the operational activities of the hospital is one of the interesting accounting problems for The Eirviromental Management Accounting (EMA) is a technique that emphasizes efficiency and effectiveness in the use of resources and is part of a wider management control system. This research method used qualitative method with case study. RSUD Dr.H. Slamet Martodjirjo Pamekasan has implemented Regulation of Minister of Trade Regulation No.64 of 2013 on the implementation of accounting based on full accrual in government in 2015 for example, has done the process of identification, recognition of measurement, recording, presentation and also disclosure. In RSUD Dr.H. Slamet Martodjirjo Pamekasan recognizes the environmental costs that occur as operational costs using the basic accrual method. Environmental accounting can support income accounting, financial accounting as well as internal business managerial accounting. Environmental accounting helps companies and other organizations raise their confidence and beliefs in relation to a more equitable assessment. Environmental accounting becomes important to consider as well as possible because environmental accounting is part or sub-accounting. Disclosure of policies relating to environmental management issues in the notes to the financial statements of RSUD Dr.Slamet Martodjirjo Pamekasan shows that the costs incurred for waste management are combined with similar accounts.Keywords :Eviromental Management Acoounting